2011
DOI: 10.1111/j.1399-3038.2011.01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated inflammatory markers at preschool age precede persistent wheezing at school age

Abstract: We demonstrated that 5 yr old children with persistent wheeze already had elevated exhaled inflammatory markers at preschool age compared to never wheezers, indicating augmented airway inflammation in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Many noninvasive techniques of airway inflammation, such as the composition of exhaled breath condensate, are not yet able to predict the persistence of asthma symptoms in preschool children. 60 Addition of the API to measurement of the exhaled breath condensate pH improved its performance substantially in discriminating atopic and nonatopic 5-year-olds with wheeze. 61 Fifth, better characterization of the genetic risk might improve the prediction of asthma.…”
Section: Recommendations To Improve Asthma Prediction In Preschool Chmentioning
confidence: 99%
“…Many noninvasive techniques of airway inflammation, such as the composition of exhaled breath condensate, are not yet able to predict the persistence of asthma symptoms in preschool children. 60 Addition of the API to measurement of the exhaled breath condensate pH improved its performance substantially in discriminating atopic and nonatopic 5-year-olds with wheeze. 61 Fifth, better characterization of the genetic risk might improve the prediction of asthma.…”
Section: Recommendations To Improve Asthma Prediction In Preschool Chmentioning
confidence: 99%
“…One study simultaneously tested the presence of several cytokines, chemokines and soluble adhesion molecules in the EBC of asthmatic children and controls, finding these molecules significantly increased in the asthmatic subjects [85]. Interestingly, five-year-old children with persistent wheeze had higher exhaled inflammatory marker levels than those who had never wheezed, indicating a greater airway inflammation in the former already at preschool age [86].…”
Section: Other Biomarkers In Ebcmentioning
confidence: 99%
“…Since many years clinical scientists are trying to find markers predicting asthma. A recent study has shown that inflammatory markers, including many interleukins (IL-2, IL-4, IL-8 and IL-10) are elevated in the exhaled breath condensate already during the pre-clinical phase anticipating wheezing [63]. Furthermore, perinatal factors may affect lung maturity and contribute to cause wheezing and asthma.…”
Section: Prediction and Preventionmentioning
confidence: 99%